Accountability in Crisis: The Sponsorship Scandal and the Office of the Comptroller General in Canada - Free, Clinton (Journal of business ethics, 2009)
For much of the last 50 years, a key platform animating public sector reform in Canada and elsewhere has been that efficiency and effectiveness can be achieved by adapting private sector financial management methods and practices. We argue that the recent re-establishment of the Office of the Comptroller General (OCG) of Canada represents a key element of a program of strengthening financial accountability that has emerged within the Canadian Federal Government. Although this program is longstanding and is associated Canada’s implementation of new public management initiatives, it has recently drawn particular sustenance from the sponsorship scandal in Canada. We demonstrate that the reincarnated OCG, re-established amid a rhetoric of “modernization” and of “strengthening” accountability, has a wide-ranging mandate to enhance financial and audit controls, create financial standards, nurture professional development, and oversee government spending. We explore some of the consequences of this development and of the broader financial accountability mechanisms introduced in response to the Sponsorship scandal within the Canadian public sector.